Polymyxin Acute Kidney Injury: a case of severe tubulopathy - Goldin,Lucas Alexandre de Mello (2022)
Abstract Polymyxins are antibiotics developed in the 1950s. Polymyxin-induced neurotoxicity has been often described in medical literature. The same cannot be said of nephrotoxicity or tubulopathy in particular. This report describes the case of a patient prescribed polymyxin B to treat a surgical wound infection, which led to significant increases in fractional excretion of calcium, magnesium, and potassium and subsequent persistent decreases in the levels of these ions, with serious consequences for the patient. Severe hypocalcemia, hypomagnesemia, and hypokalemia may occur during treatment with polymyxin. Calcium, magnesium and potassium serum levels must be monitored during treatment to prevent life-threatening conditions.